2018
DOI: 10.3168/jds.2017-14170
|View full text |Cite
|
Sign up to set email alerts
|

Continuous 11-week feeding of reduced-fat distillers grains with and without monensin reduces lactation performance of dairy cows

Abstract: This study investigated the effects of continuous feeding of high inclusion of reduced-fat corn distillers grains with solubles with and without monensin on dry matter intake (DMI), production, milk fatty acid profile, and plasma AA profile in lactating cows. The experiment was conducted for 12 wk (1-wk covariate, 2-wk diet adaptation, and 9-wk experimental period of data collection) with 36 Holstein cows in a randomized complete block design. Cows were blocked by parity, days in milk, and milk yield and assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 47 publications
5
18
0
Order By: Relevance
“…However, in growing bulls fed grass-based diets, DM digestibility estimated using iNDF differed from TC and was dependent on the pore size of the incubation bag used (Huhtanen et al, 1994). Since then, bags with a pore size of 25 µm have been widely used (Lee et al, 2012;Morris et al, 2018;Velásquez et al, 2018), and our study confirmed that iNDF with the 25-µm incubation bags accurately estimated fecal outputs and apparent digestibility of DM, OM, and N compared with TC. When comparing AIA and TC, Lee and Hristov (2013) reported an underestimation of fecal output of approximately 15%.…”
Section: Effect Of Markers On Fecal Output and Digestibilitymentioning
confidence: 56%
“…However, in growing bulls fed grass-based diets, DM digestibility estimated using iNDF differed from TC and was dependent on the pore size of the incubation bag used (Huhtanen et al, 1994). Since then, bags with a pore size of 25 µm have been widely used (Lee et al, 2012;Morris et al, 2018;Velásquez et al, 2018), and our study confirmed that iNDF with the 25-µm incubation bags accurately estimated fecal outputs and apparent digestibility of DM, OM, and N compared with TC. When comparing AIA and TC, Lee and Hristov (2013) reported an underestimation of fecal output of approximately 15%.…”
Section: Effect Of Markers On Fecal Output and Digestibilitymentioning
confidence: 56%
“…The experiment was carried out at the Ohio Agricultural Research and Development Dairy Center (Wooster, OH). Information about animals, experimental design, and dietary treatments were described in de-tail in our previous study (Morris et al, 2018). Briefly, 36 (9 primiparous and 27 multiparous) Holstein cows (average ± SD at the beginning of the trial: milk yield = 44.2 ± 8.1 kg/d; DIM = 80 ± 31 d; BW = 675 ± 74 kg) were blocked into groups of 3 (n = 12) by parity, DIM, and milk yield.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…Although this resulted in a decrease in dietary Ca content in the DG diets (Table 1), Ca supply exceeded NRC (2001) requirements. Further information about dietary composition is available in our previous study (Morris et al, 2018). The experiment consisted of a diet adaptation period for 2 wk and a 9-wk experimental period (wk 1 through 9 refers to the 9-wk experimental period).…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…In the case of Hubbard et al (2009), a high-protein corn product increased milk and FCM yields, and a high-protein distillers grain corn product decreased milk protein concentration in another case (Kelzer et al, 2009). Reduced-fat distillers grains maintained (Castillo-Lopez et al, 2014;Morris et al, 2018) or increased milk yield (Ramirez-Ramirez et al, 2016) but decreased 3.5% FCM, fat, and protein yields in a more recent study (Morris et al, 2018). Cows fed a diet with corn gluten meal as the primary protein source, compared with soybean meal, produced similar quantities of milk and FCM but produced less milk protein in early lactation (Wohlt et al, 1991).…”
Section: Discussionmentioning
confidence: 95%
“…The fermentation process results in spent grains known as distillers grains with solubles (DGS), which have a CP concentration of 27 to 31% (Belyea et al, 2004;Liu, 2011). Removal of fat from DGS marginally increases CP concentration (34%; Wang et al, 2007;Morris et al, 2018), and removal of bran and germ components enhances the efficiency of ethanol production and increases CP concentration to more than 40% (Corredor et al, 2006;Robinson et al, 2008). Distillers grains have successfully been fed to beef (Klopfenstein et al, 2008) and dairy cattle (Kelzer et al, 2009;Schingoethe et al, 2009) as a protein source, and the inclusion has become more common as ethanol production grows.…”
Section: Introductionmentioning
confidence: 99%